A robust NNP‐type ruthenium (II) complex for alcohols dehydrogenation to esters and pyrroles. (26th November 2019) - Chai, Huining; Zhang, Guangyao; Tan, Weiqiang; Ma, Jiping
Abstract : A Ru (II) complex bearing pyridyl‐based benzimidazole‐phosphine tridentate NNP ligand was synthesized and structurally characterized by NMR, IR. The complex can efficiently and selectively catalyze the acceptorless dehydrogenation of primary alcohols to esters under relatively mild conditions and the synthesis of pyrroles by means of the reactions of secondary alcohols and β‐amino alcohols through acceptorless deoxygenation condensation. Abstract : A Ru (II) complex bearing pyridyl‐based benzimidazole‐phosphine tridentate NNP ligand exhibited excellent catalytic activity in acceptorless dehydrogenation to esters and pyrroles.